2014
DOI: 10.1016/j.cell.2014.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Developmentally Silenced Globin Genes by Forced Chromatin Looping

Abstract: Summary Distal enhancers commonly contact target promoters via chromatin looping. In erythroid cells, the locus control region (LCR) contacts β-type globin genes in a developmental stage-specific manner to stimulate transcription. Previously, we induced LCR-promoter looping by tethering the self-association domain (SA) of Ldb1 to the β-globin promoter via artificial zinc fingers. Here, we show that targeting the SA to a developmentally silenced embryonic globin gene in adult murine erythroblasts triggered its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
329
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 386 publications
(350 citation statements)
references
References 52 publications
21
329
0
Order By: Relevance
“…Because LDB1 also has been reported to interact with other transcription factors, it is tempting to suggest a potentially general role for LDB1 in regulating cell typespecific, enhancer-dependent gene-expression programs. LDB1-mediated promoter:enhancer looping has been reported in the β-globin locus based on the homodimerization of LDB1 occupying both enhancer and promoter sites (22)(23)(24). Our data show that, in corticotropes, LDB1 can mediate looping to promoters without detectable promoter LDB1 binding.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Because LDB1 also has been reported to interact with other transcription factors, it is tempting to suggest a potentially general role for LDB1 in regulating cell typespecific, enhancer-dependent gene-expression programs. LDB1-mediated promoter:enhancer looping has been reported in the β-globin locus based on the homodimerization of LDB1 occupying both enhancer and promoter sites (22)(23)(24). Our data show that, in corticotropes, LDB1 can mediate looping to promoters without detectable promoter LDB1 binding.…”
Section: Discussionmentioning
confidence: 62%
“…LDB1 was postulated to play an important role in promoter:enhancer looping events and as a coactivator in several systems (21)(22)(23)(24)(33)(34)(35). To investigate its roles in gene transcription and in promoter:enhancer looping events in the POMC lineage, we performed GRO-seq after Ldb1 knockdown and observed that, of 3,378 genes down-regulated by siLdb1, 927 transcription units are located in direct proximity to the LDB1-occupied enhancers.…”
Section: Ldb1mentioning
confidence: 99%
See 1 more Smart Citation
“…27 In addition, the sequential looping of the LCR is also responsible for the switch between embryonic, fetal (HbF) and HbA ( Figure 2A). [31][32][33][34] The pattern of expression of the b-globin gene has also been a subject of intense investigations since the switching between HbF and HbA represents an important biological phenomenon and an exemplary model to understand how gene expression is regulated during development. In humans, the switching between the expression of g-globin and b-globin gene occurs in the first three months after birth ( Figure 1B).…”
Section: Globin Synthesis Erythropoiesis and Iron Metabolism: A Compmentioning
confidence: 99%
“…[61][62][63][64][65] In particular, the important role of Ldb1 in globin gene regulation has been emphasized by the observation that this protein is able to reactivate the silenced mouse embryonic globin and the human g-globin genes when fused to an artificial zinc finger tethering Ldb1 onto their promoters ( Figure 2B). 32,34 It has been shown that this artificial zinc finger-Ldb1 fusion protein is able to force the LCR-holocomplex to loop onto the promoter recognized by the zinc finger moiety. 32,34 This repositioning of the LCR is sufficient to re-activate the expression of otherwise silenced globin genes.…”
mentioning
confidence: 99%